2002
DOI: 10.1177/00343552020450040201
|View full text |Cite
|
Sign up to set email alerts
|

Income

Abstract: Existing theories of career development have been criticized in the rehabilitation literature for having questionable applicability to persons with disabilities. Given the diversity of disabilities and of persons with disabilities, the authors doubt that a generally applicable theory can be developed. They propose a viable alternative to guide rehabilitation counseling practice: a framework that posits that the career development of individuals (including those with disabilities) at any given point in their li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 25 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Getzel and Thoma (2008) learned that college students with disabilities identified setting career-related goals as a key factor in postsecondary success. However, Beveridge, Craddock, Liesener, Stapleton, and Hershenson (2002) found that young adults with disabilities often lack access to career-related activities and have limited understanding about the world of work, thus making it difficult for these students to make career-related decisions.…”
Section: Transition Planning Procedures Are Beginning To Include Post...mentioning
confidence: 99%
“…Getzel and Thoma (2008) learned that college students with disabilities identified setting career-related goals as a key factor in postsecondary success. However, Beveridge, Craddock, Liesener, Stapleton, and Hershenson (2002) found that young adults with disabilities often lack access to career-related activities and have limited understanding about the world of work, thus making it difficult for these students to make career-related decisions.…”
Section: Transition Planning Procedures Are Beginning To Include Post...mentioning
confidence: 99%
“…Mentoring has been useful, offering professional stimulation to faculty members and provided formal and informal networks of communication (Gardiner et al, 2007). Similarly, Beveridge et al (2002), Direnzo et al (2010) highlighted, much of the research on mentoring looks directly to career outcomes and the expectancy that mentoring will produce certain outcomes for protégés. The importance of having a mentor in career development has found by many researches in variety of context.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown the relationship between career advancement with organizational factors such as mentoring (Higgins & Kram, 2001;Scandura & Williams, 2001;Lankau & Scandura, 2002;Godshalk & Sosik, 2003;Simmonds & Zammit, 2010;Lease, 2004;De Janasz & Sullivan, 2004;Kasprisin et al, 2003;Packard, 2003;Bozionelos, 2006;Gardiner et al, 2007;Arokiasamy & Ismail, 2008). In the literature, researchers have investigated the relationship between self-efficacy with mentoring (Allen et al, 2004;Chan & Ho, 2008;Beveridge, et al, 2002;Sambunjak, Straus, & Marusic, 2006). Furthermore, there are studies that have illustrated the relationship between self-efficacy and career advancement (Duffy et al, 2006;Schyns & von Collani, 2002;Day & Allen, 2004;Valcour & Ladge, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research suggests that it is of great importance for students with disabilities to "be socialized to set their career goals consistent with their abilities and interests" (Feldman, 2004, p. 271). The INCOME (i.e., Imagining, Informing, Choosing, Obtaining, Maintaining, and Exiting) intervention developed by Beveridge et al (2002) provides helpful guidance for individuals with different forms of disabilities to reach developmental goals.…”
Section: Personal Constraintsmentioning
confidence: 99%